2019
DOI: 10.1111/ctr.13689
|View full text |Cite
|
Sign up to set email alerts
|

Use of mTOR inhibitor as prophylaxis for cytomegalovirus disease after kidney transplantation: A natural experiment

Abstract: Objectives To describe the incidence of cytomegalovirus (CMV) infection/disease in kidney transplant recipients receiving an mTOR‐inhibitor‐containing immunosuppressive regimen without prophylactic CMV treatment. Methods This single‐center retrospective cohort analysis included all de novo kidney transplant recipients (09/15/2015‐07/31/2017) receiving 3 mg/kg single dose of rabbit antithymocyte globulin induction, tacrolimus, everolimus, and prednisone. Preemptive therapy was initiated only in patients deemed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…All patients received immunosuppressive therapy and six patients used ganciclovir for treatment of CMV disease, consisted of intravenous 5 mg/kg b.i. d. ganciclovir, adjusted for renal function [16].…”
Section: Study Populationmentioning
confidence: 99%
“…All patients received immunosuppressive therapy and six patients used ganciclovir for treatment of CMV disease, consisted of intravenous 5 mg/kg b.i. d. ganciclovir, adjusted for renal function [16].…”
Section: Study Populationmentioning
confidence: 99%
“…In a recent randomized trial, we observed a low incidence of AR (9.4%) and CMV infection (4.7%) in patients receiving 3 mg/kg of rATG induction, low‐dose TAC, and everolimus in KTR receiving no pharmacological prophylaxis for CMV infection [18]. This immunosuppressive regimen, previously with basiliximab and currently with rATG induction, has also been used in low immunological risk KTR [19].…”
Section: Introductionmentioning
confidence: 99%
“…All participants received induction therapy to prevent acute rejection consisting of a 500 mg methylprednisolone bolus intraoperatively, and, except for living HLA‐identical kidney transplants, a single 3 mg/kg dose anti‐thymocyte globulin (r‐ATG) within the first 24 hours after graft revascularization. Tacrolimus or cyclosporine, prednisone and either azathioprine, mycophenolate or mTOR inhibitors were all administered from day 1 16 . In the first observation period (15‐20 days), the dose of immunosuppressants was still being adjusted, while in the second period (45‐60 days) the maintenance dose was already established for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Preemptive therapy or treatment of CMV disease consisted of intravenous 5 mg/kg b.i.d. ganciclovir, adjusted for renal function 16 …”
Section: Methodsmentioning
confidence: 99%